Guided Inquiry Berbasis Self-Regulated Learning: Upaya Menstimulasi Keterampilan Inkuiri Ilmiah Melalui Investigasi Cacing Tanah : (Guided Inquiry Based on Self-Regulated Learning: An Effort to Stimulate Scientific Inquiry Skills Through Earthworm Investigations) - Aulia, Rifda Yulfi; Setiono, Setiono; Nuranti, Gina (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
The low level of students' scientific inquiry skills and independent learning (Self-Regulated Learning/SRL) poses a real challenge in Biology learning. This study aims to examine the effect of the SRL-based Guided Inquiry model through earthworm investigation on students' scientific inquiry skills. The research method used was a quasi-experiment with a Nonequivalent Control Group Design. Sampling was carried out using a saturated sampling technique (total sampling), with a sample size of 15 students in the experimental class and 25 students in the control class. Data were collected through an inquiry ability test instrument, observation sheets for learning implementation and SRL, as well as student response questionnaires. The results of the hypothesis testing on N-Gain data using the Independent Samples T-Test showed a significance value of P = 0.025 (P < 0.05) with a good N-Gain category. These results prove that the SRL-based Guided Inquiry model is more effective in improving students' inquiry skills compared to the control class. The success of this intervention was supported by the optimal implementation of syntax (91.67%), the appearance of SRL in the good category (77.50%), and highly positive student responses (93.12%). Overall, the combination of this guided model and self-regulation is recommended to stimulate students' scientific performance with a gradual assistance modification (scaffolding) during the initial hypothesis formulation phase. Abstrak. Rendahnya Scientific Inquiry Skills dan kemandirian belajar (Self-Regulated Learning) siswa menjadi tantangan nyata dalam pembelajaran Biologi. Penelitian ini bertujuan untuk menguji pengaruh model Guided Inquiry berbasis SRL melalui investigasi cacing tanah terhadap Scientific Inquiry Skills siswa. Metode penelitian yang digunakan adalah kuasi eksperimen dengan desain Nonequivalent Control Group Design. Pengambilan sampel dilakukan menggunakan teknik sampling jenuh (total sampling), dengan jumlah sampel 15 siswa di kelas eksperimen dan 25 siswa di kelas kontrol. Data dikumpulkan melalui instrumen tes Scientific Inquiry Skills, lembar observasi keterlaksanaan pembelajaran dan SRL, serta angket respon siswa. Hasil uji hipotesis data N-Gain menggunakan Independent Samples T-Test menunjukkan nilai signifikansi sebesar P=0,025 (P<0,05) dengan kategori N-Gain yang baik. Hasil ini membuktikan bahwa model Guided Inquiry berbasis SRL lebih efektif dalam meningkatkan Scientific Inquiry Skills siswa dibanding kelas kontrol. Keberhasilan ini didukung oleh keterlaksanaan sintaks yang optimal (91,67%), kemunculan SRL berkategori baik (77,50%), serta respon siswa yang sangat positif (93,12%). Secara keseluruhan, perpaduan model Guided Inquiry dan Self-Regulated Learning ini direkomendasikan untuk menstimulus performa ilmiah siswa dengan modifikasi bantuan bertahap (scaffolding) pada fase perumusan dugaan awal.